A method for improving the solid solubility of chromium in high entropy carbide ceramics

By adding excess chromium oxide to high-entropy carbide ceramics and combining carbon-thermal reduction and discharge plasma sintering technology, the problem of insufficient solid solubility of chromium elements is solved, and the improvement of solid solubility of chromium elements and the improvement of material performance in high-entropy carbide ceramics is achieved.

CN116947495BActive Publication Date: 2025-03-25HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310697934.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2025-03-25
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

In the prior art, the solid solubility of chromium elements in high-entropy carbide ceramics is difficult to reach or close to the equimolar ratio, resulting in the impact of material properties.

Method used

By adding excess chromium oxide powder on the basis of component equimolar ratios, combined with carbon thermal reduction technology and technical means to control the sintering temperature of discharge plasma, the solid solubility of chromium elements in high-entropy carbide ceramics is improved.

Benefits of technology

The solid solubility of chromium elements in high-entropy carbide ceramics is achieved to reach an equimolar ratio or close to equimolar ratio, and a high-entropy carbide ceramic with good densification and a single crystal structure is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116947495B_ABST
    Figure CN116947495B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the solid solubility of chromium in high entropy carbide ceramics. The method comprises the following steps: mixing multi-component transition metal oxide powders containing excess chromium oxide by ball milling, forming the obtained mixed powder by pressing, and carbon thermally reducing the obtained compact to obtain a presolid solution; and spark plasma sintering the presolid solution at a temperature close to the melting point of chromium oxide to obtain high entropy carbide ceramics. The method improves the solid solubility of chromium in high entropy carbide ceramics by combining technical means such as adding excess chromium oxide powder, adopting carbon thermal reduction, and controlling the ultra-high temperature spark plasma sintering temperature, so that high entropy carbide ceramics containing chromium with an equiatomic ratio or close to an equiatomic ratio can be prepared, and the obtained product has good densification and a single crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for improving the solid solubility of chromium in high entropy carbide ceramics, and specifically to a method for improving the solid solubility of chromium in a high entropy carbide ceramic system by adding excess chromium oxide and combining technical means such as carbon thermal reduction and controlling spark plasma sintering temperature, and belongs to the field of high temperature ceramic materials. Background Art

[0002] High entropy carbide ceramics contain a variety of metal cations in equiatomic or near-equiatomic ratios. They are mainly transition metal carbides and have a single crystal structure. High entropy carbide ceramic materials have high melting points, excellent mechanical properties and high temperature stability, high hardness, good wear resistance and oxidation resistance. Based on these characteristics, high entropy carbide ceramics can be well used in harsh environments, such as aviation engine parts, corrosive gas filtration devices, and hypersonic aircraft leading edges. In terms of material preparation methods, current reports have shown that high entropy carbide ceramic blocks can be prepared by solid phase sintering; high entropy carbide ceramic powders can be prepared by liquid phase precursor method; in addition, high entropy carbide ceramics can be prepared by magnetron sputtering, mechanically induced carbon diffusion, carbon thermal reduction technology combined with spark plasma sintering.

[0003] In the periodic table, metal elements of Group IV (Ti, Zr, Hf) and Group V (V, Nb, Ta) can form high entropy carbide ceramics with a single rock salt structure at room temperature and high temperature, while metal elements of Group VI (Cr, Mo, W) cannot form a single rock salt phase high entropy carbide ceramics at room temperature. Based on the entropy formation capacity value of compounds containing Group VI metal elements calculated by density functional calculation, the researchers proved that the elements of this group can be dissolved in a single-phase rock salt structure, that is, studies have shown that chromium elements are dissolved in other group element systems to form high entropy carbide ceramics with a single crystal structure. At present, there are few studies on chromium elements in high entropy carbide ceramics. Chromium elements can improve the performance of materials in high entropy carbide ceramics. For example, in terms of hardness, chromium elements are dissolved in the carbide lattice, causing local lattice distortion, resulting in solid solution strengthening, and improving the hardness of the material. Related studies have confirmed that high entropy carbide ceramics containing chromium elements have higher nanoindentation hardness than high entropy carbide ceramics without chromium elements. However, the current research on high entropy carbide ceramics basically suffers from the phenomenon of chromium loss, which causes the metal elements to fail to reach an equimolar ratio or close to an equimolar ratio, which will affect the performance of the material. Therefore, how to improve the solid solubility of chromium in high entropy carbide ceramics has become one of the current research hotspots.

[0004] In order to improve the solid solubility of chromium in high entropy carbide ceramics, researchers are currently improving it in the following ways. First, by adding an excess of chromium carbide powder on the basis of the equiatomic ratio of the components, the loss of chromium content during the preparation process is compensated to achieve an equiatomic ratio or close to an equiatomic ratio; the relevant research team used spark plasma sintering technology to prepare high entropy carbide ceramics (CrZrNbHfTa)C, in which the amount of chromium carbide (Cr3C2) added was changed to obtain experimental samples with a gradient change in chromium content; the research results showed that in the high entropy carbide ceramic samples containing chromium, the atomic ratio of chromium relative to all metals was only about 2.5at%, and the atomic ratio did not change significantly with the increase in the amount of chromium carbide (Cr3C2) added. The second is to improve the preparation process of high-entropy carbide ceramics. Chromium carbide (Cr3C2) is easy to volatilize at high temperature. The chromium content in high-entropy carbide ceramics prepared by traditional spark plasma sintering is usually lower than the initial design value. Therefore, Shen Ping's team from Jilin University and other teams used ultrafast high-temperature technology to synthesize high-entropy carbide ceramics (TiCrZrNbTaVMoW)C. The high temperature duration in ultrafast high-temperature technology is very short, which is beneficial to reduce the volatilization of chromium and increase the solid solubility of chromium in high-entropy carbide ceramics. After testing, the chromium content (6.06at%) in the prepared octal high-entropy carbide ceramics was close to the design value (6.25at%).

[0005] There are still many problems to be solved in the above method of improving the solid solubility of chromium in high entropy ceramics:

[0006] 1. The method of increasing the solid solubility of chromium in high entropy carbide ceramics by adding excessive chromium carbide powder did not achieve the expected effect, that is, the equiatomic ratio was not reached, and the addition of excessive chromium carbide powder did not change the solid solubility of chromium in high entropy carbide ceramics.

[0007] 2. The method of improving the solid solubility of chromium in high entropy carbide ceramics by improving the preparation process of high entropy carbide ceramics. Although it can improve the solid solubility of chromium in high entropy carbide ceramics, current relevant research shows that the amount of chromium-containing high entropy carbide ceramic products that can be prepared in a single time is extremely small, and the chromium element has serious segregation phenomenon; and the preparation equipment requirements are extremely high, making it difficult to achieve mass production. Summary of the invention

[0008] In view of the fact that the solid solubility of chromium in the currently disclosed high-entropy carbide ceramic system containing chromium element cannot reach an equimolar ratio or a near equimolar ratio, and the existing improvement methods have the above-mentioned technical problems, the purpose of the present invention is to provide a method for improving the solid solubility of chromium element in high-entropy carbide ceramics. The method is based on the equimolar ratio of components, and then adds an excess of chromium oxide powder, and combines carbon thermal reduction technology with controlling the spark plasma sintering temperature and other technical means to achieve the improvement of the solid solubility of chromium element in high-entropy carbide ceramics. High-entropy carbide ceramics containing chromium element in an equimolar ratio or a near equimolar ratio can be prepared, and the obtained product has good densification and a single crystal structure.

[0009] In order to achieve the above technical objectives, the present invention provides a method for improving the solid solubility of chromium in high entropy carbide ceramics, the method comprising the following steps:

[0010] 1) mixing a multi-component transition metal oxide powder and a carbon powder by ball milling to obtain a mixed powder; the multi-component transition metal oxide powder comprises a chromium oxide powder, and the amount of the chromium oxide powder is in excess relative to the theoretical molar amount, and the amounts of other metal oxide powders except the chromium oxide powder are measured according to the theoretical molar amount;

[0011] 2) pressing the mixed powder into a compact to obtain a green compact;

[0012] 3) Carbothermally reducing the compact to obtain a presolid solution;

[0013] 4) Spark plasma sintering the presolid solution at 70% to 90% of the melting point of chromium oxide to obtain high entropy carbide ceramics.

[0014] The high entropy carbide ceramic of the present invention refers to a multi-component metal carbide containing a plurality of metal cations in equiatomic ratios or nearly equiatomic ratios and having a single crystal structure, wherein the atomic fraction of each metal element in the system is greater than 5% and not more than 35%. The metal elements in the high entropy carbide ceramics currently studied mainly include metal elements of Group IV (Ti, Zr, Hf), Group V (V, Nb, Ta) and Group VI (Cr, Mo, W). The present invention specifically describes the high entropy carbide ceramic formed by transition metal elements of V, Cr, Ta, and Ti in equiatomic ratios as an example. The type of high entropy carbide ceramics involved in the present invention is not limited to the exemplified (TiCrTaV)C high entropy carbide ceramics, but is used as an example to illustrate how to improve the solid solubility of chromium in high entropy carbide ceramics.

[0015] The key to improving the solid solubility of chromium in high entropy carbide ceramics in the technical solution of the present invention is to further add an excess of chromium oxide powder on the basis of an equimolar ratio of the components, and combine the carbon thermal reduction technology with the technical means of strictly controlling the spark plasma sintering temperature to achieve the improvement of the solid solubility of chromium in high entropy carbide ceramics. Excess chromium oxide consumes more carbon atoms for carbonization during the carbon thermal reduction process, which can reduce the presence of free carbon in the product. On this basis, spark plasma sintering is carried out under temperature conditions close to the melting point of chromium oxide, which is conducive to the discharge of residual chromium oxide in the carbon thermal reduction process and the reduction of unnecessary impurities in the product. At the same time, chromium oxide will form a liquid phase, which is conducive to the densification sintering of the material, and promotes material diffusion and densification process, thereby obtaining a single-phase structure high entropy carbide ceramic with good densification.

[0016] As a preferred solution, the amount of the chromium oxide powder is 15% to 87.5% in excess of the theoretical molar amount. The theoretical molar amount refers to the molar amount required for the high entropy carbide ceramic according to the composition design. If the amount of the chromium oxide powder is no more than (less than) 15% in excess of the theoretical molar amount, the chromium element loss phenomenon is serious during the preparation process, and the lower addition amount will not make up for the low solid solubility caused by the chromium loss. If the amount of the chromium oxide powder is higher than 87.5% in excess of the theoretical molar amount, due to the presence of too much excess chromium oxide, the presolid solution undergoes partial sintering and densification during the carbon thermal reduction process, which is not conducive to the uniform distribution of elements; and when a certain amount of carbon powder is reduced, when the excess degree of chromium oxide addition is too high, more chromium oxide will remain in the presolid solution after carbon thermal reduction, and more liquid phase will be generated in ultra-high temperature spark plasma sintering, which has an adverse effect on the product and equipment. Therefore, as a more preferred solution, the amount of the chromium oxide powder is 25% to 75% in excess of the theoretical molar amount.

[0017] As a preferred solution, the ball milling mixing includes wet ball milling and drying, and the ball milling conditions are: the ball-to-material mass ratio is 3:1-10:1 (mass ratio), the ball milling medium is anhydrous ethanol, the ball milling speed is 200r / min-400r / min, forward rotation is 5min-60min, reverse rotation is 5min-60min, forward rotation and reverse rotation are not stopped, and the total ball milling time is 12-36h; the drying conditions are: temperature is 40℃-100℃, and time is 6-20h. Further preferred ball milling conditions are: ball-to-material ratio is 3:1-5:1, ball milling speed is 200r / min-300r / min, forward rotation is 30min-60min, reverse rotation is 30min-60min, forward rotation and reverse rotation are not stopped, and the total ball milling time is 12-24h. Further preferred drying conditions are: temperature is 60℃-90℃, and time is 8-12h. Under the optimal high-energy ball milling conditions, transition metal oxides and carbon powders can be evenly mixed, and the mixture can be given a higher system energy, which is beneficial to the subsequent carbon thermal reduction and spark plasma sintering process. Under the optimal drying conditions, the ball milling medium anhydrous ethanol can be completely volatilized during the ball milling wet mixing process, reducing the impurity content and improving the purity of the product.

[0018] As a preferred solution, the pressing conditions are: unidirectional pressing, a pressure of 20 to 150 MPa, and a load holding time of 5s to 30s. Further preferred pressing conditions are: a pressure of 30 to 80 MPa (most preferably 40 to 60 MPa), and a load holding time of 10s to 20s. The pressing process is implemented by a unidirectional hydraulic press. Under the preferred pressing conditions, the pressed green sheet can maintain a relatively complete shape after carbothermal reduction, which is conducive to the collection of carbothermal reduction products, the discharge of impurities in the carbothermal reduction products, and the transition metal oxides can be fully carbonized. The pressing process is implemented by a unidirectional hydraulic press. When the pressure is too small, the pressed green sheet is too loose and fragile in the subsequent carbothermal reduction, which is not conducive to collection; when the pressure is too large, the pressed green sheet is too dense, which is not conducive to achieving full carbonization. Under the preferred pressing conditions, the pressed green sheet can maintain a relatively complete shape after carbothermal reduction, which is conducive to the collection of carbothermal reduction products, the discharge of impurities in the carbothermal reduction products, and the transition metal oxides can be fully carbonized.

[0019] As a preferred solution, the carbon thermal reduction conditions are: under vacuum conditions, at a heating rate of 5°C / min to 50°C / min, the temperature is increased to 600°C to 1200°C, after keeping warm for 0.25h to 1h, the temperature is further increased to 1600°C to 2000°C, the temperature is kept warm for 0.25h to 1h, and then the temperature is cooled to room temperature. Further preferred carbon thermal reduction conditions are: under vacuum conditions, at a heating rate of 5°C / min to 20°C / min, the temperature is increased to 800°C to 1100°C, after keeping warm for 0.5h to 1h, the temperature is further increased to 1700°C to 1900°C, the temperature is kept warm for 0.5h to 1h, and then the temperature is cooled to room temperature. Under the preferred solution, on the basis of the atomic ratio of the multi-component components, an excess of chromium oxide powder is added, which is conducive to consuming more carbon atoms during the carbon thermal reduction process, reducing the presence of free carbon in the prepared high entropy carbide ceramics, and at the same time increasing the solid solubility of chromium in the product. During the carbon thermal reduction process, the temperature is first kept at about 1000°C to eliminate other impurities and reduce the impact of impurities on the vacuum degree in the furnace. The temperature is then kept at about 1800°C to fully carbonize the metal oxides.

[0020] As a preferred solution, the conditions of the spark plasma sintering are: pressure of 10-50 MPa, sintering temperature of 1600°C-2000°C, and holding time of 2-20 min. Further preferred conditions of the spark plasma sintering are: pressure of 30-50 MPa, sintering temperature of 1700°C-1900°C, and holding time of 5-15 min. Under the preferred spark plasma sintering conditions, a certain amount of chromium oxide will remain in the pre-solidified powder after carbon thermal reduction. If the spark plasma sintering temperature is close to the melting point of chromium oxide, for example, it reaches 80% of its melting point (the temperature measured during sintering is lower than the actual temperature inside the material), the chromium oxide will overflow the material in the form of liquid phase, which is helpful for the densification sintering of the material, and can promote the diffusion of the material and the densification process, that is, to obtain a material with good density. In addition, it can also reduce oxygen impurities in the product and improve the purity of the product, thereby improving the performance of the material. The spark plasma sintering process includes plasma activation, resistance heating and pressurization. It has a fast sintering temperature rise rate and a short sintering time, which can effectively control the grain growth of the material. Compared with other sintering technologies, its products have better density and good mechanical properties. At the same time, by strictly controlling the sintering temperature, it is conducive to the discharge of excess chromium oxide without reducing the solid solubility of chromium. If the sintering temperature is closer to or higher than the melting point of chromium oxide, chromium will overflow in large quantities, reducing the solid solubility of chromium.

[0021] The amount of carbon powder used in the present invention is measured based on the metal oxide, and each metal atom requires a corresponding carbon atom.

[0022] The purity of the multi-component transition metal oxide powder of the present invention is greater than 99.9wt%.

[0023] The purity of the reduced carbon powder of the present invention is greater than 99.9 wt %.

[0024] The particle size of the multi-component transition metal oxide powder of the present invention is in the range of 500nm to 1μm.

[0025] The pre-solidified powder of the present invention is crushed and then loaded into a mold for spark plasma sintering. The crushing process uses an agate mortar, and the mesh size of the sieve is 60 to 200 mesh, that is, 250 μm to 75 μm. More preferably, the mesh size of the sieve is 100 to 120 mesh, that is, 150 μm to 125 μm. The particle agglomeration phenomenon can be eliminated by crushing, which can effectively prevent the phenomenon of component segregation in the product and affect the performance of the product.

[0026] Compared with the prior art, the technical solution of the present invention has the following obvious technical advantages:

[0027] (1) The technical solution of the present invention, based on the use of excess chromium oxide, can effectively improve the solid solubility of chromium in high entropy carbide ceramics by adopting carbon thermal reduction and spark plasma sintering technology near the melting point of chromium oxide, thereby obtaining a single-phase structure high entropy carbide ceramic with an equimolar ratio or a near equimolar ratio and good density.

[0028] (2) The technical solution of the present invention adopts carbon thermal reduction technology, which can reduce the presence of oxygen elements and free carbon to obtain high-purity high-entropy carbide ceramics.

[0029] (3) The technical solution of the present invention can realize the high-yield production of high-entropy carbide ceramics, and can solve the technical problems such as the extremely small amount of existing high-entropy carbide ceramic products, the serious segregation of chromium elements, the extremely high requirements for preparation instruments, and the difficulty in achieving mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is an EDS analysis chart of the product after spark plasma sintering in Example 1 of the present invention.

[0031] Figure 2 This is the EDS analysis chart of the product after carbon thermal reduction in Comparative Example 2.

[0032] Figure 3 This is the EDS analysis diagram of the product after spark plasma sintering in Comparative Example 2. DETAILED DESCRIPTION

[0033] In order to facilitate the understanding of the present invention, the content of the present invention will be described more comprehensively and carefully below in combination with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0034] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0036] Example 1

[0037] A method for improving the solid solubility of chromium in high entropy carbide ceramics of the present invention comprises the following steps:

[0038] (1) Cr2O3 (purity 99.9%), V2O5 (purity 99.9%), Ta2O5 (purity 99.9%), TiO2 (purity 99.9%) and carbon powder with a particle size of 500nm to 1μm, except for a small amount of unavoidable impurity elements, the raw materials do not contain other metallic impurity elements; according to the method based on the atomic ratio of the components and the total weight of the powder of 100g, first weigh 14.72g of V2O5 powder, 12.30g of Cr2O3 powder, 35.76g of Ta2O5 powder, 12.92g of TiO2 powder and 24.3g of carbon powder respectively; 0g; in addition, 50% more chromium element is added on the basis of the atomic ratio of the components, that is, 6.09g more Cr2O3 powder is added on the basis of 12.30g (total 18.39g), the weighed powder is placed in a cemented carbide ball mill for wet mixing, the ball-to-material mass ratio is 4:1, the ball milling medium is 100ml of anhydrous ethanol (industrial anhydrous ethanol), the ball milling speed is 250r / min, forward rotation is 60min, reverse rotation is 60min, and there is no pause between forward and reverse rotation. The total ball milling time is 20h, and the mixed powder after ball milling needs to be dried, the drying temperature is 90℃, and the drying time is 10h.

[0039] (2) The mixed powder dried in step (1) is formed into a cylindrical green compact using a hydraulic press at a pressure of 40 MPa; the green compact is placed in a carbothermic reduction furnace, and the vacuum degree in the furnace is first evacuated to 6 Pa by a mechanical pump, and then carbothermic reduction is performed. The heating rate in the carbothermic reduction furnace is 10°C / min, and the temperature is raised to 1000°C and kept for 1 hour, and then the temperature is further raised to 1800°C and kept for 1 hour, and then the temperature is lowered to room temperature to obtain a pre-solidified powder, which is crushed and sieved through 100 mesh to control the particle size to be less than 150 μm.

[0040] (3) The carbon thermal reduction pre-solidified powder obtained in step (2) is subjected to spark plasma sintering, the spark plasma sintering temperature is controlled at 1800° C., the temperature is kept at 1800° C. for 10 minutes, and the sintering pressure is controlled at 40 MPa.

[0041] The product of this embodiment is tested by the organization observation method and the element analysis method. The present invention can obtain a high entropy carbide ceramic with a nearly equiatomic ratio. The solid solubility of chromium in the product reaches 11.08at%, and the solid solubility of other elements are 11.49at% of vanadium, 12.50at% of tantalum, and 12.05at% of titanium. The elements of the product are evenly distributed, and there is no free carbon. It can be observed from the EDS analysis of the ultra-high temperature spark plasma sintered product of this embodiment that Figure 1 After relevant tests, the elastic modulus of the product is 350.51GPa and the Vickers hardness HV1 is 2468.

[0042] Example 2

[0043] A method for improving the solid solubility of chromium in high entropy carbide ceramics of the present invention comprises the following steps:

[0044] (1) Cr2O3 (purity 99.9%), V2O5 (purity 99.9%), Ta2O5 (purity 99.9%), TiO2 (purity 99.9%) and carbon powder with a particle size of 500nm to 1μm, except for a small amount of unavoidable impurity elements, the raw materials do not contain other metallic impurity elements; according to the method based on the atomic ratio of the components and the total weight of the powder of 100g, 14.72g of V2O5 powder, 12.30g of Cr2O3 powder, 35.76g of Ta2O5 powder, 12.92g of TiO2 powder and 10.5g of carbon powder were weighed. 24.30g; in addition, 75% more chromium element is added on the basis of the equal atomic ratio, that is, 9.12g more Cr2O3 powder is added on the basis of 12.30g (total 21.42g); the weighed powder is placed in a cemented carbide ball mill for wet mixing, the ball-to-material mass ratio is 4:1, the ball milling medium is 100ml of anhydrous ethanol, the ball milling speed is 250r / min, forward rotation is 60min, reverse rotation is 60min, and there is no pause between forward and reverse rotation. The total ball milling time is 20h, and the mixed powder after ball milling needs to be dried, the drying temperature is 90℃, and the drying time is 10h.

[0045] (2) The mixed powder dried in step (1) is formed into a cylindrical green compact using a hydraulic press at a pressure of 40 MPa; the green compact is placed in a carbothermic reduction furnace, and the vacuum degree in the furnace is first evacuated to 6 Pa by a mechanical pump, and then carbothermic reduction is performed. The heating rate in the carbothermic reduction furnace is 10°C / min, and the temperature is raised to 1000°C and kept for 1 hour, and then the temperature is further raised to 1800°C and kept for 1 hour, and then the temperature is cooled to room temperature to obtain a pre-solidified powder, which is crushed and sieved with 100 mesh, that is, the particle size is controlled to be below 150 μm.

[0046] (3) The carbon thermal reduction pre-solidified powder obtained in step (2) is subjected to spark plasma sintering, the spark plasma sintering temperature is controlled at 1850° C., the temperature is kept at 1850° C. for 10 minutes, and the sintering pressure is controlled at 40 MPa.

[0047] The product of this embodiment is tested by the organization observation method and the element analysis method. The present invention can obtain a high entropy carbide ceramic with a nearly equiatomic ratio. The solid solubility of chromium in the product is 8.79at%, and the solid solubility of other elements are 11.54at% of vanadium, 12.61at% of tantalum, and 12.28at% of titanium. The product clearly observes the residual chromium oxide after carbon thermal reduction, but there is basically no free carbon, and the other elements are evenly distributed. After relevant tests, the elastic modulus of the product is 311.50GPa, and the Vickers hardness HV1 is 2423.

[0048] Comparative Example 1

[0049] The only difference from Example 1 is that no additional 7.60 g of Cr2O3 powder is added. Other operations and conditions are exactly the same as those in Example 1.

[0050] The product of this embodiment is tested by the organization observation method and the element analysis method. The present invention can obtain a high entropy carbide ceramic with low chromium solid solubility. After carbon thermal reduction, all elements in the product are distributed in a segregated manner. In addition, the solid solubility of chromium in the product is only 7.34at%, which is lower than the solid solubility of other elements (vanadium is 8.66at%, tantalum is 9.00at%, and titanium is 8.77at%). The elements in the product are evenly distributed. After relevant tests, the elastic modulus of the product is 333.88GPa and the Vickers hardness HV1 is 2177.

[0051] The amount of chromium oxide powder in this comparative example is not added in excess, and the components are prepared in equal molar ratios; in terms of the preparation process, it is consistent with the process and its parameters of Example 1 of the present invention. The solid solubility of chromium in this comparative example is low, mainly because chromium will be lost during carbon thermal reduction and ultra-high temperature spark plasma sintering. Since this comparative example does not add excessive chromium oxide, there is no excess chromium to make up for the loss of chromium, resulting in a low solid solubility of chromium in the product of this example. Compared with Example 1 of the present invention, the hardness of this comparative example is relatively low, mainly because this comparative example has a lower solid solubility of chromium, and chromium is dissolved in the carbide lattice, causing local lattice distortion, resulting in solid solution strengthening, and improving the hardness of the product.

[0052] Comparative Example 2

[0053] The difference from Comparative Example 1 is that the temperature is not kept at 1000° C. during the carbon thermal reduction process, and the temperature used for the carbon thermal reduction is 2050° C., and other conditions are the same.

[0054] The results show that the solid solubility in this comparative example is lower than that in comparative example 1. The main reason is that a higher carbonization temperature is adopted in the carbon thermal reduction process, which makes the chromium element more volatile and causes more serious chromium element loss. This shows that in order to increase the solid solubility of chromium in high entropy carbide ceramics, it is not appropriate to select too high a carbonization temperature in the carbon thermal reduction process.

[0055] The product of this embodiment was tested by tissue observation and elemental analysis, and it was clearly observed that free carbon existed in the high entropy ceramic powder obtained by this method, which can be observed from the EDS analysis of the product after carbon thermal reduction of this embodiment. Figure 2 The solid solubility of chromium in the product is only 5.56at%, which is much lower than the solid solubility of other elements (vanadium is 10.11at%, tantalum is 9.94at%, and titanium is 10.21at%); all elements are evenly distributed, and no oxygen impurities are obviously observed, which can be observed from the EDS analysis of the product after ultra-high temperature spark plasma sintering in this embodiment. Figure 3 .

Claims

1. A method for increasing the solid solubility of chromium in high entropy carbide ceramics, characterized in that: The following steps are involved: 1) wet-milling and drying multi-component transition metal oxide powder and carbon powder to obtain a mixed powder; The multi-component transition metal oxide powder includes chromium oxide powder, and the amount of the chromium oxide powder is 15% to 87.5% in excess of the theoretical molar amount, and the amounts of other metal oxide powders except the chromium oxide powder are measured according to the theoretical molar amount; 2) Pressing the mixed powder into a compact to obtain a green compact; 3) Carbothermally reducing the pressed green sheet to obtain a presolid solution; the carbothermally reducing conditions are: under vacuum conditions, heating to 600°C~1200°C at a heating rate of 5°C / min~50°C / min, keeping the temperature for 0.25h~1h, then heating to 1600°C~2000°C, keeping the temperature for 0.25h~1h, and then cooling to room temperature; 4) The presolid solution is subjected to ultra-high temperature spark plasma sintering to obtain high entropy carbide ceramics; the spark plasma sintering conditions are: pressure of 10-50 MPa, sintering temperature of 1600° C.-2000° C., and holding time of 2 min-20 min.

2. A method for improving the solid solubility of chromium in high entropy carbide ceramics according to claim 1, characterized in that: The amount of the chromium oxide powder used is 25% to 75% in excess of the theoretical molar amount.

3. The method for improving the solid solubility of chromium in high entropy carbide ceramics according to claim 1, characterized in that: The conditions for wet ball milling are: ball-to-material mass ratio of 3:1-10:1, ball milling medium is anhydrous ethanol, ball milling speed is 200r / min-400r / min, forward rotation is 5min-60min, reverse rotation is 5min-60min, forward rotation and reverse rotation are continuous, and the total ball milling time is 12-36h; the conditions for drying are: temperature is 40°C-100°C, and time is 6-20h.

4. A method for improving the solid solubility of chromium in high entropy carbide ceramics according to claim 1, 2 or 3, characterized in that: the pressing conditions are: unidirectional pressing, a pressure of 20~150MPa, and a load holding time of 5s~30s.

5. A method for improving the solid solubility of chromium in high entropy carbide ceramics according to claim 4, characterized in that: the pressing conditions are: unidirectional pressing, a pressure of 40-60 MPa, and a load holding time of 10s-20s.

6. A method for improving the solid solubility of chromium in high entropy carbide ceramics according to claim 1, characterized in that: the conditions of the carbon thermal reduction are: under vacuum conditions, at a heating rate of 5°C / min~20°C / min, the temperature is increased to 800°C~1100°C, kept warm for 0.5h~1h, then continued to increase the temperature to 1700°C~1900°C, kept warm for 0.5h~1h, and then cooled to room temperature.

7. A method for improving the solid solubility of chromium in high entropy carbide ceramics according to claim 1, characterized in that: the conditions of the spark plasma sintering are: pressure of 30-50 MPa, sintering temperature of 1700° C.-1900° C., and holding time of 5 min-15 min.

Citation Information

Patent Citations

  • Super-hard five-component transition metal carbide single-phase high-entropy ceramic material and preparation method thereof

    CN110194667A